New species from family Gasterosteidae in ichthyofauna of the Caspian Sea basin - M. M. Shikhshabekov; R. M. Barkhalov; N. I. Rabazanov (Юг России: экология, развитие)
There is described a new genus and species - Gasterosteus Aculeatus for the Dagestan part of the Middle Caspian from the genus Gasterosteus species Aculeatus, which differs from other kinds of family Gasterosteidae by presence of three needles on the back part of the body and by some ecological features. This species is well enough described in other southern reservoirs. In comparison of external attributes of the three-needle stickle-back of the Caspian and other southern reservoirs no special differences are revealed.